A Neonate With MuSK Congenital Myasthenic Syndrome Presenting With Refractory Respiratory Failure - Shen, Yanhua; Wang, Bo; Zheng, Xia; Zhang, Wenwen; Wu, Hailan; Hei, Mingyan (Frontiers in Pediatrics, 2020)
This was a Chinese neonatal congenital myasthenic syndromes case caused by muscle skeletal receptor tyrosine kinase gene mutations, which have not been recorded in the Human Gene Mutation Database. The newborn girl had refractory respiratory failure from birth to death, and failed extubation 7 times. She had 2 heterozygous mutations: a nonsense mutation c.2062C>T (p.Q688X) inherited from father and a missense mutation c.2324T>C (p.F775S) inherited from mother, which was predicted pathogenic and harmful by bioinformatic softwares SIFT, PolyPhen_2 and REVEL. She positively responded to Neostigmine, but her parent quitted treatment when Pyridostigmine Bromide (2mg/kg Q12h) had been given for 8 days. She died 2 days after she was taken home by her parents on age of 56 days.